2019
DOI: 10.5539/mas.v13n5p48
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder (ASD); Symptoms, Causes, Diagnosis, Intervention, and Counseling Needs of the Families in Jordan

Abstract: Autism Spectrum Disorder (ASD) is one of the most confusing disorders for which not only no exact cause has been identified, but also no definitive cure has been found yet. Autism is a disorder that is usually observed on the child at an early age, affecting various developmental aspects. Its development is abnormal. It shows an imbalance in its social interaction, characterized by repetition of certain behavioral patterns and challenges in verbal and nonverbal communication with others. Over the last few deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Knowledge part of the study instrument consist of two types of questions: truefalse questions (1,3,5,6,7,9,13,14,15,16) with two responses one correct and one incorrect responses, the correct response was coded with (2) points and the incorrect response coded with (1) point. and multiple-choice questions (2,4,8,10,11,12) with four responses one correct and three incorrect responses the correct response was coded with (2) points and the incorrect response coded with (1) point. Regarding attitude part used three-point Likert scale (agree, Uncertain, disagree) and scoring was (3) points for agree, (2) point for Uncertain and (1) point for disagree.In this study, when measuring knowledge of the caregivers, it is found that the MS: Mean of Scores was poor at MS = 1-1.33 and fair at MS = 1.34-1.67 while it considered good at MS ≥ 1.68.While, in measuring attitude of the caregivers, it is found that the MS: Mean of Scores was poor at MS = 1-1.33 and fair at MS = 1.34-2.66 while it considered good at MS ≥ 2.67.…”
Section: Rating and Scoringmentioning
confidence: 99%
“…Knowledge part of the study instrument consist of two types of questions: truefalse questions (1,3,5,6,7,9,13,14,15,16) with two responses one correct and one incorrect responses, the correct response was coded with (2) points and the incorrect response coded with (1) point. and multiple-choice questions (2,4,8,10,11,12) with four responses one correct and three incorrect responses the correct response was coded with (2) points and the incorrect response coded with (1) point. Regarding attitude part used three-point Likert scale (agree, Uncertain, disagree) and scoring was (3) points for agree, (2) point for Uncertain and (1) point for disagree.In this study, when measuring knowledge of the caregivers, it is found that the MS: Mean of Scores was poor at MS = 1-1.33 and fair at MS = 1.34-1.67 while it considered good at MS ≥ 1.68.While, in measuring attitude of the caregivers, it is found that the MS: Mean of Scores was poor at MS = 1-1.33 and fair at MS = 1.34-2.66 while it considered good at MS ≥ 2.67.…”
Section: Rating and Scoringmentioning
confidence: 99%
“…On the other hand, the confusion matrix also produces accurate precision, recall, and f1-score values, where precision according to equation (15) represents the accuracy of the requested data with the results given by the model. Recall depicts the success of the model in finding information according to equation (14). In addition, the f1score is used if the FN and FP values are not close to symmetric, so the f1-score is used as a reference following equation (17).…”
Section: Linear Discriminant Analysis (Lda) Resultsmentioning
confidence: 99%
“…They typically experience restrictions on social communication and often try to socialize in a very structured manner. It is important to understand that these issues are not a sign of disinterest or reluctance to socialize but arise from their struggle to use appropriate social, communication, and language skills (Adnyani & Munir, 2022;Ali et al, 2019;Minaabad, 2020). Autism is classified as a spectrum disorder due to the various types of symptoms and severity.…”
Section: Introductionmentioning
confidence: 99%
“…Some programs and strategies aim to address the main challenges of social communication in autism, for instance, social skills training programs that have shown moderate helpful evidence. This can involve the participation of family members and friends, lengthening the sessions, incorporating targeted activities to enhance self-awareness of one's emotional states, and utilizing more visual aids (Ali et al, 2019;Lord et al, 2020;Padmadewi & Artini, 2017). Providing educational support to students with ASD early on is crucial for their long-term academic success and overall quality of life as adults (Kumar & Behera, 2021).…”
Section: Introductionmentioning
confidence: 99%